Kebaya - a producer's perspective - Beh, Wen Jing (Nanyang Technological University, 2022)
Kebaya is a short narrative film about a young air stewardess (Ting) who has to navigate her role of a caregiver for her estranged grandmother, while managing and dealing with her relationship with her distant father(David). This story was inspired by Trevor’s (Writer and Director of Kebaya) sister, who was an air stewardess, and she had previously shared her worries of not being able to physically care for her family, as her job requires her to travel frequently.